Cool Japan guide fun in the land of manga, lucky cats, and ramen - Denson, Abby (Tuttle Publishing, 2014)
Traveling to Japan has never been so much fun -- visit the land of anime, manga, cosplay, hot springs and sushi! This full-color graphic novel guidebook explores Japanese culture from a cartoonist's perspective. Cool Japan Guide takes you on a fun tour from the high-energy urban streets of Tokyo to the peaceful Zen gardens and Shinto shrines of Kyoto and introduces you to the exciting worlds of Japanese food, the otaku (geek) culture of Japan, the complete Japanese shopping experience, the world's biggest manga, anime, and cosplay festivals, the best travel apps for Japan, and more.